2018
DOI: 10.30651/jmlt.v1i2.1496
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Genetik Nyamuk Vektor Filariasis Culex quinquefasciatus Say, 1823 (Diptera: Culicidae) di Kota dan Kabupaten Pekalongan Dengan Metode PCR-RAPD

Abstract: Mosquito Culex quinquefasciatus is a vector of nematode worms, namely Wuchereria bancrofti which is the cause of filariasis in tropical and subtropical countries. Distributed of Cx. quinquefasciatus is widely in Indonesia with differences the geographical, resulting in the adaptation to the environment and may results in a high variation, both phenotypic (morphology) and genotypic (genetic) variation. This study aims was to determine the genetic diversity of mosquitoes Cx.quinquefasciatus as vector filariasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
2
1
2
Order By: Relevance
“…15 However, in Jenggot Village (Pekalongan City) it is showed moderate diversity and more various the mosquitoes genus, which were 5 of mosquito genera, which were genera of Culex, Aedes, Armigeres, Anopheles, and the genus of Lutzia. This finding is different from the results of the research conducted by Arimurti (2008) which concluded that the Cx. quiqueefas ciatus mosquito from Pekalongan city and Regency showed a high level of diversity with polymorphism reaching 100% based on the RAPD-PCR method.…”
Section: Diversitycontrasting
confidence: 99%
See 1 more Smart Citation
“…15 However, in Jenggot Village (Pekalongan City) it is showed moderate diversity and more various the mosquitoes genus, which were 5 of mosquito genera, which were genera of Culex, Aedes, Armigeres, Anopheles, and the genus of Lutzia. This finding is different from the results of the research conducted by Arimurti (2008) which concluded that the Cx. quiqueefas ciatus mosquito from Pekalongan city and Regency showed a high level of diversity with polymorphism reaching 100% based on the RAPD-PCR method.…”
Section: Diversitycontrasting
confidence: 99%
“…quiqueefas ciatus mosquito from Pekalongan city and Regency showed a high level of diversity with polymorphism reaching 100% based on the RAPD-PCR method. 16 The Culex and Aedes are culicinae mosquito, they were belong to Culicidae family and the order of Diptera. Morphologically the adult female mosquito in the genera of Culex and Aedes may distinguished mostly by the head and thorax character.…”
Section: Diversitymentioning
confidence: 99%
“…Dari semua penjelasan diatas, Penjelasan yang berpengaruh adalah karena lingkungan antara kota dan pekalongan tidak jauh berbeda. Suhu, kelembaban antara kota dan kabupaten Pekalongan tidak berbeda, seperti misalnya hasil penelitian menunjukkan bahwa keaneragaman nyamuk antara Kota Pekalongan dan Kabupaten Pekalongan sama (Arimurti, 2018). Sehingga penelitian ini memiliki kelemahan karena komparasi kota dan desa tidak memiliki disparitas kondisi yang jauh.…”
Section: Perbedaan School Well Being Antara Mbs Kota Dan Desaunclassified
“…Culex quinquefasciatus ialah nyamuk vektor Lymphatic Filariasis 33 terutama sebagai vektor W. bancrofti di wilayah Pulau Jawa. 23,34 Habitat Culex quinquefasciatus lebih banyak ditemukan di berbagai habitat spesifik dibandingkan nyamuk Culex lainnya. Hal ini sejalan dengan penelitian tentang habitat nyamuk Cx.…”
Section: Bahan Dan Metodeunclassified